Komunikasi Krisis Zara Dalam Menangani Krisis Kampanye ‘The Jacket’ - Lilik Sumarni; Dewi Suryaningsih; Vivi Alayda Rahmat; Widya Maulya; Salsabila Salsabila (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
The communication crisis experienced by Zara in the "The Jacket" campaign highlights the critical importance of social and cultural sensitivity in marketing strategies. The controversy that arose sparked negative public reactions, underscoring the necessity for companies to exercise greater caution in delivering messages aligned with societal values. This study analyzes Zara's approach to addressing the crisis through the framework of Situational Crisis Communication Theory (SCCT). Communication strategies involving apologies, transparency, and concrete corrective actions are identified as key elements in restoring reputation. Additionally, internal evaluations of creative processes and heightened cultural awareness in campaign development were conducted to prevent similar crises in the future. This study emphasizes the significance of speed, clarity, and empathy in crisis management, as well as the strategic use of social media to rebuild public trust.